Validation of a spectrophotometric method for quantification of xanthone in biodegradable nanoparticles - Teixeira, M (2004)
Xanthone has been incorporated for the first time in nanoparticles of poly(D,L-lactide-co-glycolide) (PLGA). For this purpose the estimation of xanthone content in the nanoparticles is a crucial tool for guaranteeing the reliability of the results. Thus, a simple spectrophotometric method was validated according to USP25 and ICH guidelines for its specificity, linearity, accuracy and precision. The method was found to be specific for xanthone in the presence of nanoparticle excipients. The calibration curve was linear over the concentration range of 0.5 to 4.0 mug/mL (r > 0.999). Recovery of xanthone from nanoparticles ranged from 86.5 to 95.9%. Repeatability (intra-assay precision) and intermediate precision were found to be acceptable with relative standard deviations values (RSD) ranging from 0.3 to 3.0% and from 1.4 to 3.1%, respectively. The method was found to be suitable for the evaluation of xanthone content in nanoparticles of PLGA.